Autonomous bacterial localization and gene expression based on nearby cell receptor density. Issue 1 (22nd January 2013) - Wu, Hsuan‐Chen; Tsao, Chen‐Yu; Quan, David N; Cheng, Yi; Servinsky, Matthew D; Carter, Karen K; Jee, Kathleen J; Terrell, Jessica L; Zargar, Amin; Rubloff, Gary W; Payne, Gregory F; Valdes, James J; et al.
Abstract : Escherichia coli were genetically modified to enable programmed motility, sensing, and actuation based on the density of features on nearby surfaces. Then, based on calculated feature density, these cells expressed marker proteins to indicate phenotypic response. Specifically, site‐specific synthesis of bacterial quorum sensing autoinducer‐2 (AI‐2) is used to initiate and recruit motile cells. In our model system, we rewired E. coli's AI‐2 signaling pathway to direct bacteria to a squamous cancer cell line of head and neck (SCCHN), where they initiate synthesis of a reporter (drug surrogate) based on a threshold density of epidermal growth factor receptor (EGFR). This represents a new type of controller for targeted drug delivery as actuation (synthesis and delivery) depends on a receptor density marking the diseased cell. The ability to survey local surfaces and initiate gene expression based on feature density represents a new area‐based switch in synthetic biology that will find use beyond the proposed cancer model here. Abstract : Escherichia coli were engineered to enable programmed motility, sensing and phenotypic response to the density of epidermal growth factor receptor expressed on the surface of cancer cells. Synopsis: Escherichia coli were engineered to enable programmed motility, sensing and phenotypic response to the density of epidermal growth factor receptor expressed on the surface of cancer cells. Bacteria were engineered to display targeted motility through AI‐2‐mediated chemotaxis. Recruitment of motile bacteria was achieved by site‐specific synthesis of quorum sensing autoinducers using anti‐EGFR nanofactories. Threshold‐based switching of bacterial gene expression was controlled by AI‐2 quorum sensing. The engineered 'bacterial dirigible' represents a new means for targeted drug delivery and may have multiple applications wherein bacterial cells are designed to carry out specified tasks.